The role of digital trust in digital maturity models - Horváth, József György (Vezetéstudomány / Budapest Management Review, 2025)
The success of digital transformation is closely linked to the presence of digital trust, which significantly influences organizations’ ability to adopt new technologies. Digital maturity models are used to assess organizations’ digital capabilities; however, they vary in how explicitly they address the dimension of digital trust. This study explores how digital trust is represented across various digital maturity models. Through a qualitative analysis of 25 models, the research identifies key components – such as data security, technological reliability, organizational transparency, and employee competencies – contributing to building digital trust. The results suggest that only six models address digital trust explicitly, while in the remaining frameworks it appears implicitly, typically as part of other dimensions. The study concludes that treating digital trust as a dedicated dimension could significantly improve the practical usability of digital maturity models, particularly by strengthening transparent and ethical technology use.